The issue of the immigrants that impact on crime rate: evidence from 17 European countries / Nur Diana Farahim Abd Rahim - Abd Rahim, Nur Diana Farahim (2019)
This study was focused on the issues of the immigrants that impact on the crime rate in the 17 European countries. Measurement was done on several independent variables consists of four variables which was police report per capital, populations of the immigrants, unemployment’s and social problem (drugs disorder). Besides that, the dependent variable for this research was homicides (crime rate) Hence, this study used the secondary data to collect the data. The data were collected from four websites which is World Bank Development Database, World Development Indicator (WDI), Pordata (WSA) and Ourworldindata which utilize for the period of the 24 year (1993-2017). After collected all the data, it has been analysed and following data was mentioned by macroeconomics indicators was aggregated into a panel data set encoded in STATA SE 14.0. Type of study used in this research is a casual study. It is undertaken to measure the relationship between the variables. Casual study is used identify whether change in one variable will causes change to another variable. As for this research, it will test on how unemployment’s, populations, social problems and police report per capita will impact on homicides (crime rate). The findings discovered that the crime rates have given the negative relationship between population and homicides, and unemployment and homicides. Meanwhile, it gives positive relationship between police report per capita and drugs (social problem) with homicides.